Management of Kuin Floating Market Tourism Development, North Banjarmasin District - Neti Rosiana Fadilah; Mohdari Mohdari; Muhammad Fahmi; Syafril Syafril; Yuliani Yuliani (Universitas Pahlawan Tuanku Tambusai, 2023)
This research was conducted to describe the development of Kuin Floating Market tourism and the efforts made to overcome problems in the development of Kuin Floating Market Tourism. The research design used in this study is qualitative research. The location of research was carried out at the tourist destination Kuin Floating Market. The data collection techniques used in this study were documentation, participatory observation, and in-depth interviews. In checking the validity of the data obtained by the researcher, triangulation of the sources and methods used is used. Meanwhile, researchers' data analysis techniques are data reduction, data presentation, and data verification. The results showed that: 1) Development of Kuin Floating Market tourism. Several aspects of development carried out in Kuin Floating Market tourism, including (a) Promotion, (b) Accessibility, and (c) Tourism Area. 2) Efforts made to overcome problems in the development of Kuin Floating Market Tourism include (a) Submitting budgets and collaborating with private parties and (b) Providing understanding to the local community.